Therapeutic Communication of Nurses in the Surgical Treatment Room of RSUD Arifin Nu’mang - Julita, Ema; Rahagia, Rasi; Fajar Cahya, Mochamad Robby; Resti Wijayanti, Fitria Eka; Malaha, Naomi; Rasyid, Djusmadi; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The quality of health services is what refers to the level of perfection of health services in causing satisfaction in each patient. The more perfect the satisfaction felt, the better the quality of health services. In organizing efforts to maintain the quality of health services in hospitals, it is inseparable from the nursing profession which plays an important role because nursing services ensure the existence of high-quality nursing care in quality control programs in hospitals, considering that nursing services take place continuously for 24 hours a day. The nursing service team provides services to clients in accordance with professional beliefs and established standards, this shows that the nursing services provided are always safe services and can meet the needs and expectations of clients. The purpose of this study was to determine the relationship between educational background with the implementation of therapeutic communication of nurses in the surgical treatment room of Arifin Nu'mang Hospital Sidenreng Rappang. This research methodology is a non-experimental research with descriptive research type, with observational research form. The research design in this study is Cross Sectional. Data in this study were obtained by finding respondents who fit the inclusion criteria then giving or distributing questionnaires to respondents. From the univariate analysis, the results obtained between verbal therapeutic communication as much as 63.5% who perceived well and non-verbal nurses as much as 85% who perceived well. The conclusion in this study is that the client's perception of the nurse's therapeutic communication shows quite good results.